al-‘Arabiyah Linnasyi'in: Analysis of Teaching Materials By Mahmud Ismail Shini, Nashif Musthofa Abdul 'Aziz, and Mukhtar Thahir Husain - Hidayatullah, Andri (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2021)
Learning resources are an important aspect in the learning process, various models of arabic learning resources are raised by experts in accordance with the results of their research and development. In line with that the book "al-'Arabiyyah Linnasyi'in" is one of the various sources of Arabic language learning that is widely used in educational institutions, but how the method of writing this book has not been revealed so that it is interesting for Arabic teachers to make it as a source of learning, therefore this research aims to know the form of presentation used in the teaching book "al-'Arabiyyah Linnasyi'in". This research uses qualitative descriptive approach, the data source used is the book "al-'Arabiyyah Linnasyi'in", as well as other works related to the preparation of textbooks. The data is collected by carefully reading the themes related to the focus of the research. The research data was analyzed using critical analysis. The results prove that the preparation of the book al-'Arabaiyyah Linnasyi'in compiled by nazhariyyah al-wihdah method and theory, this finding is based on the material on the aspect of vocabulary, sentence structure in terms of organizing material, presentation of vocabulary, presentation of structures arranged without fundamental separation, in addition the material is arranged in stages so as to allow users of this book to understand it sequentially.